Hydrophilic interaction liquid chromatography in the separation of a moderately lipophilic drug from its highly polar metabolites--the cardioprotectant dexrazoxane as a model case - Kovaříková, Petra; Stariat, Ján; Klimeš, Jiří; Hrušková, Kateřina; Vávrová, Kateřina (Journal of chromatography. A, 2011)
This paper presents a systematic study of the retention behavior of a model bisdioxopiperazine drug, dexrazoxane (DEX) and its three polar metabolites (two single open-ring intermediates-B and C and an EDTA-like active compound ADR-925) on different stationary phases intended for hydrophilic interaction liquid chromatography (HILIC). The main aim was to estimate advantages and limitations of HILIC in the simultaneous analysis of a moderately lipophilic parent drug and its highly polar metabolites, including positional isomers, under MS compatible conditions. The study involved two bare silica columns (Ascentic Express HILIC, Atlantis HILIC) and two stationary phases with distinct zwitterionic properties (Obelisc N and ZIC HILIC). The chromatographic conditions (mobile phase strength and pH, column temperature) were systematically modified to assess their impact on retention and separation of the studied compounds. It was found that the bare silica phases were unable to separate the positional isomers (intermediates B and C), whereas both columns with zwitterionic properties (Obelisc N and ZIC HILIC) were able to separate these structurally very similar compounds. However, only ZIC HILIC phase allowed appropriate separation of DEX and all its metabolites to a base line within a single run. A mobile phase composed of a mixture of ammonium formate (0.5 mM) and acetonitrile (25:75, v/v) was suggested as optimal for the simultaneous analysis of DEX and its metabolites on ZIC HILIC. Thereafter, HILIC-LC-MS analysis of DEX and all its metabolites was performed for the first time to obtain basic data about the applicability of the suggested chromatographic conditions. Hence, this study demonstrates that HILIC could be a viable solution for the challenging analysis of moderately polar parent drug along with its highly polar metabolites including the ability to separate structurally very similar compounds, such as positional isomers.
Keywords: glycin; razoxan; Ethylenediamines; Hydrogen-Ion Concentration; teplota; Tandem Mass Spectrometry; kardiovaskulární látky; Chromatography, Liquid; chemické modely; Temperature; tandemová hmotnostní spektrometrie; Cardiovascular Agents; Glycine; Models, Chemical; Razoxane; koncentrace vodíkových iontů; chromatografie kapalinová; hydrofobní a hydrofilní interakce; ethylendiaminy; Hydrophobic and Hydrophilic Interactions